1988
DOI: 10.1111/j.1439-0434.1988.tb04452.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Acquired Resistance Induced in Tobacco Plants by Localized Virus Infection Does Not Operate Against Challenging Viruses That Infect Systemically

Abstract: Localized infections produced by tobacco necrosis virus (TNV) or tomato mosaic virus (ToMV) in White Burley tobacco induced a systemic acquired resistance in upper, uninoculated leaves. This resistance was effective against challenge infection by TNV or ToMV but not by potato virus Y, necrotic strain (PVYn), tobacco mosaic virus (TMV) or tobacco rattle virus (TRV), viruses giving systemic infections. Systemic acquired resistance against TNV or ToMV was expressed as a reduction in lesion size but not in viral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
3
12
0
1
Order By: Relevance
“…In this case, C. quinoa presented genetic factors that avoided the CABMV systemic movement and was able to respond to the inducers positively. Results similar to those presented here were obtained by Pennazio and Roggero (1988) Several studies have shown systemic resistance induction against local lesion viruses, but the treatment's inefficiency against systemic invasion by viruses is of little value to the disease control. The aphid vectors in the field transmit the CABMV in a non-persistent way, through the feeding-probe with their stylets.…”
Section: Discussionsupporting
confidence: 78%
“…In this case, C. quinoa presented genetic factors that avoided the CABMV systemic movement and was able to respond to the inducers positively. Results similar to those presented here were obtained by Pennazio and Roggero (1988) Several studies have shown systemic resistance induction against local lesion viruses, but the treatment's inefficiency against systemic invasion by viruses is of little value to the disease control. The aphid vectors in the field transmit the CABMV in a non-persistent way, through the feeding-probe with their stylets.…”
Section: Discussionsupporting
confidence: 78%
“…Plants of asparagus bean {Vigna sesquipedalis Fruhw.) were grown from seed as previously described (PENNAZIO et al 1987). Their primary leaves were inoculated with tobacco necrosis virus (TNV) or tobacco rattle virus (TRV) (inducing inoculation).…”
Section: Plants Viruses and Inoculation Proceduresmentioning
confidence: 99%
“…Basal ethylene was determined in trifoliate induced and control leaves 3 days after inducing inoculation, after 1 h incubation in darkened sealed vials. Samples of ethylene released from leaves were determined by gas chromatography (PENNAZIO and ROGGERO 1990).…”
Section: Ethylene Efa and Free Acc Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, acquired resistance against local lesion-producing challenging viruses operates in limiting the number and size of lesions, whereas virus accumulation in these lesions does not appear to be affected (for references, see PENNAZIO and ROGGERO 1988). STEIN et al (1985), however, found that acquired resistance to TMV in N. tahacum cv.…”
mentioning
confidence: 99%